The Application of E-Court by the Panel of Judges in the Perspective of Civil Procedure Law - Rahmat, Rifki; Akib, Ma'ruf; Umar, Wahyudi (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The development of information technology has brought very significant changes in various sectors, including the legal system in Indonesia. To realize the principles of fast, simple and low-cost justice, the Supreme Court of the Republic of Indonesia issued Supreme Court Rules Number 1 of 2019 as amended by Supreme Court Rules Number 7 of 2022, in response to the demands of efficiency, transparency, and accessibility in the judicial process. However, in its implementation, there are limitations and challenges in the Supreme Court Rules.Purposes of the Research: This research aims to explore and understand e-court regulations and examine the challenges in the implementation of e-courts in the Indonesian judicial system.Methods of the Research: Using normative legal research methods with Statute approach and conceptual approach.Results Main Findings of the Research: The results of the study show that the legal basis of the panel of judges in the implementation of e-court lies in article 6 paragraph (8) and article 20 of Supreme Court Rules Number 1 of 2019 as amended by Supreme Court Rules Number 7 of 2022, as well as other legal principles that serve as guidelines for the panel of judges in the implementation of e-court. However, the use of ecourt in resolving cases electronically is not optimal, this is because there are a number of obstacles such as limited facilities and infrastructure, lack of understanding from law enforcement officials and the public about e-court, as well as legal regulations that have not been effective and other problems.